2020
DOI: 10.3390/s20092575
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mobile Emitter Location by Cooperative Swarm of Unmanned Aerial Vehicles in Various Environmental Conditions

Abstract: This paper focused on assessing the effectiveness of the signal Doppler frequency (SDF) method to locate a mobile emitter using a swarm of unmanned aerial vehicles (UAVs). Based on simulation results, we showed the impact of various factors such as the number of UAVs, the movement parameters of the emitter and the sensors on location effectiveness. The study results also showed the dependence of the accuracy and continuity of the emitter coordinate estimation on the type of propagation environment, which was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Equation (2) illustrates a simplified two-dimensional (2D) version of SDF which assumes that the sensor moves at a constant speed along a specific direction OX, i.e., , and at a specific height, i.e., Three-dimensional (3D) SDF is presented in [ 27 ]. In this case, the sensor can move in different directions with variable speed.…”
Section: Signal Doppler Frequency Location Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation (2) illustrates a simplified two-dimensional (2D) version of SDF which assumes that the sensor moves at a constant speed along a specific direction OX, i.e., , and at a specific height, i.e., Three-dimensional (3D) SDF is presented in [ 27 ]. In this case, the sensor can move in different directions with variable speed.…”
Section: Signal Doppler Frequency Location Methodsmentioning
confidence: 99%
“…Measurements [ 30 ] have shown that using ground vehicles introduces limitations to the localization procedure, including difficulties in maintaining a constant speed, changing the sensor motion direction, and multipath propagation resulting from the neighborhood of terrain obstacles [ 32 ]. The use of UAVs [ 27 , 28 ] or watercrafts [ 33 ] for this purpose provides greater opportunities, provides greater movement freedom, and improves propagation conditions by minimizing the impact of unfavorable phenomena.…”
Section: Signal Doppler Frequency Location Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the moving sensors, satellites in a group, or unmanned aerial vehicles (UAVs) in a sensor network [33,34], the transmit bandwidth cannot afford such data transmission volume. Thus, a multi-pulse cross ambiguity function (MPCAF) is proposed to reduce the data volume.…”
Section: Ktmmentioning
confidence: 99%
“…The primary difference from traditional methods is that compressed data are used for joint processing. The data volume is tiny, and it is unnecessary to restore the compressed data to the original since accurate TDOA and FDOA are obtained with (33) and (34). The results are shown in Figure 16.…”
Section: Hardware-in-the-loop Datamentioning
confidence: 99%